O04.6 Mycoplasma Genitalium- Is It a Pathogen in Acute Pelvic Inflammatory Disease (PID)?. (13th July 2013) - Wiesenfeld, H C; Hillier, S L; Meyn, L; Trucco, G; Amortegui, A; Macio, I S; Rabe, L; Cosentino, L; Darville, T
Abstract : Background: PID is a polymicrobial infectious condition of the female upper genital tract. Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT), long considered the predominant organisms involved in the pathogenesis of PID, are identified in fewer than half of U.S women diagnosed with acute PID. Mycoplasma genitalium (MG) is associated with male urethritis and some evidence suggests an association with other STD syndromes including cervicitis and PID. Our objective was to examine the association between MG and acute PID. Methods: The ACE Trial is a randomised double-blind study evaluating the value of anaerobic therapy for acute PID. At enrollment, specimens were collected from the cervix and endometrium for testing for GC, CT and MG by transcription-mediated amplification. Histology was performed on endometrial tissue. Identification of cervical and endometrial organisms was correlated with endometritis. Results: Among the 125 women diagnosed with acute PID, twenty two percent (n = 27) tested positive for M. genitalium, while CT, GC and bacterial vaginosis were present in 14%, 7% and 54%, respectively. Forty six women (37%) had histologic endometritis. Histologic endometritis was more common among those having cervical infections with GC, CT or MG than uninfected women (66% vs. 24%, p < 0.001). Among women with endometritis, GC, CT and MG were present in 17%, 30% and 36%, respectively. Endometritis was present in 71% (20/28) of women with endometrial GC, CT or MG. Endometrial identification of GC (100% vs. 34%, p < 0.05), CT (77% vs. 32%, p < 0.01) and MG (64% vs. 33%, p < 0.05) were each independently associated with endometritis. Conclusion: Mycoplasma genitalium is identified in 22% of women diagnosed with acute PID. Similar to CT and GC, the presence of MG in the endometrium is highly associated with endometritis among women diagnosed with PID. This study suggests that M. genitalium may play an important role in the pathogenesis of PID.